Effects of solution conditions on characteristics and size exclusion chromatography of pneumococcal polysaccharides and conjugate vaccines. (5th November 2016) - Hadidi, Mahsa; Buckley, John J.; Zydney, Andrew L.
Highlights: Capsular polysaccharides and vaccine conjugates studied by SEC. SEC retention volume decreases at low ionic strength for charged polysaccharides. Effective polysaccharide size controlled by intramolecular electrostatic interactions. Data in good agreement with extended model for radius of gyration. Results provide insights into properties of polysaccharides and vaccine conjugates. Abstract: Molecular properties of bacterial polysaccharides and protein-polysaccharide conjugates play an important role in the efficiency and immunogenicity of the final vaccine product. Size exclusion chromatography (SEC) is commonly used to analyze and characterize biopolymers, including capsular polysaccharides. The objective of this work was to determine the effects of solution ionic strength and pH on the SEC retention of several capsular polysaccharides from S. pneumoniae bacteria in their native and conjugated forms. The retention time of the charged polysaccharides increased with increasing ionic strength and decreasing pH due to compaction of the polysaccharides associated with a reduction in the intramolecular electrostatic interactions. The calculated radius of gyration was in good agreement with model calculations based on the worm-like chain model accounting for the increase in chain stiffness and excluded volume of the charged polysaccharide at low ionic strength. These results provide important insights into the effects of solution ionic strength on physical properties and SEC behavior of capsular polysaccharides and their corresponding conjugates.